Improvement of spreadability of grape molasses with induced crystallization for production of creamed molasses as a novel product - Ozmen, Duygu; Yildirim, Rusen Metin; Bursa, Kubra; Kian-pour, Nasim; Toker, Omer Said; Palabiyik, Ibrahim; Konar, Nevzat; Yurt, Bayram (ELSEVIER, 2023)
Induced static-crystallization of grape-molasses (GM) was successfully done via adding crystallized honey (CH) to improve the crystallization rate, crystal size and to obtain a homogeneous crystalline structure of the product with the desirable rheological and textural properties. The effect of CH concentration (5, 10, and 15%) as starter and storage time (1st, 7th, 14th, 21st, and 28th day at 14 degrees C) on the rheological, physicochemical, and crys-tallization characteristics of GM/CH blends was investigated. Flow behavior of the molasses changed to Ostwalt de Waele model from Newtonian behavior. Apparent viscosity and consistency coefficient values increased and flow behavior index decreased with crystallization. Temperature-dependent apparent viscosity at shear rate 50 s-1 was successfully described by the Arrhenius equation. As storage time increased, activation energy increased from 342.17 to 427.16 (J/mol). All samples showed liquid-like properties because the loss modulus was remarkably higher than the storage modulus. The particle-size ranged between 12.60 and 33.20 mu m with the highest value at the 15% sample. Spreadability and firmness values of samples were found to between 0.46 and 5.47 N mm and 0.094-0.195 N, respectively. Spreadability and machinability characteristics of the molasses can be improved by controlled crystallization which can positively affect consumer acceptability of the product.
Keywords: Crystallization; Grape molasses; Spreadability; Reology; Texture; RHEOLOGICAL PROPERTIES; SENSORY PROPERTIES; CHOCOLATE; PEKMEZ; MICROSTRUCTURE; STABILITY; SUGAR; COLOR; Food Science & Technology